Factors influencing the satisfaction of international postgraduate students in the Malaysian context-A literature review and a proposed model - Memon, M.A. (Canadian Center of Science and Education, 2014)
The Malaysian government is continuously striving to develop the country to become a regional education hub. Hence, higher learning institutions, especially universities, are becoming the centre of attention in order for Malaysia to achieve its desired status. Although the number of international postgraduate students in Malaysia has progressively increased, the country still needs an annual growth of 13.5 per cent to attain the target of 150,000 international students by 2015. Previous studies have reported that student satisfaction can lead to attracting new students and retaining the existing ones. Hence, it is essential for Malaysian universities to understand the factors that influence the satisfaction of students. Despite its importance, less attention has been given to the experiences and satisfaction of students in higher learning institutions in Malaysia. The key objective of this paper is to conduct a comprehensive review of the literature and develop a conceptual model that integrates several antecedents that are theoretically linked to student satisfaction. The proposed conceptual model suggests that the internal and external environment of a university, and the feedback of research supervisors are the key factors that influence the level of satisfaction among international postgraduate students. Finally, recommendations for future studies are proposed. Â© The author(s).